Avaliação de comportamento de sono e impulsividade em escolares de 15 a 17 anos do município de Canoas - RS - Molina, Thayla Jacobi (2015)
Adolescence is a stage of development with a tendency to experience a greater exposure to risk situations, an exacerbate period of impulsive behaviors and decreased sleep (exchanging the day by night), being a stage of human development in which organic and psychic changes occur. This study aimed to verify the prevalence of impulsivity and sleep behavior disorders in school students aged 15 to 17 years old and to investigate if there is an association between them. The participants of this study were students aged 15 to 17 years old, registered in high schools of Canoas, RS. The participation in the research was voluntary and spontaneous. To evaluate sleep it was used the Sleep Disturbance Scale for Children (SDSC). And to verify the impulsivity, it was used the Barratt's scale. The two scales are self-administered. The total of participants was 275 students. The chi squared test conducted to determine the relationship among impulsivity and sleep disorders showed a significant relationship among these variables, X2 (1, N = 167) = 5.498, p <, 019. The magnitude of the positive relationship between impulsivity and the probability of having sleep disorders was 18%. In this sample it was found an association with positive trend between sleep and impulsivity changes. Keywords